1995
DOI: 10.1161/01.cir.91.7.2049
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric and Biochemical Correlates of Arterial Procollagen Gene Expression During Vascular Repair After Experimental Angioplasty

Abstract: We conclude that procollagen genes are transcriptionally activated early (2 to 7 days) after angioplasty vessel injury and that collagen subsequently constitutes a major biochemical and histological component of the proliferative neointima by 30 days after angioplasty. Alterations in pathways regulating procollagen metabolism may also contribute to the accumulation of extracellular matrix and growth of the neointima in the late repair phase after vessel wall injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…[29,30,31] In fact, the fibrosis of the aortic wall would be due to the presence of collagen, [32] which is dominant in the proliferative intima. [33] Our qualitative and quantitative study on the phenotypic expression of collagen has shown that cultured SMCs of the normal and diabetic Psammomys obesus synthesise more type I than type III collagen, in accord with the results of Layman et al [34] [36] have shown that SMC produced essentially collagen I and III. Ang et al [37] have observed an activation of mRNA coding 1 (I) and czl (III) chains of procollagen in rabbit synthetic SMCs. Compared with control, the diabetic state induced a large increase in type I and type III collagen biosynthesis and secretion.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[29,30,31] In fact, the fibrosis of the aortic wall would be due to the presence of collagen, [32] which is dominant in the proliferative intima. [33] Our qualitative and quantitative study on the phenotypic expression of collagen has shown that cultured SMCs of the normal and diabetic Psammomys obesus synthesise more type I than type III collagen, in accord with the results of Layman et al [34] [36] have shown that SMC produced essentially collagen I and III. Ang et al [37] have observed an activation of mRNA coding 1 (I) and czl (III) chains of procollagen in rabbit synthetic SMCs. Compared with control, the diabetic state induced a large increase in type I and type III collagen biosynthesis and secretion.…”
Section: Discussionsupporting
confidence: 86%
“…Karim et al. [33] have noted equally an increase of mRNA coding for 01 (I) zl (III) chains after 30 days of experimental angioplasty. Katsuda et al [32] have shown the coexistence of the two phenotypes in the intimal lesions, but type I collagen would stimulate the SMC migration, t38] During the development of the atherosclerotic process, many authors showed that collagen molecules are also subject to qualitative alterations.…”
Section: Discussionmentioning
confidence: 94%
“…Restenosis emerges from the migration of smooth muscle cells from the arterial media to the intima, where they change to a synthetic phenotype, produce extracellular matrix, and proliferate, thereby resulting in a stenosis within the vessel lumen (21,22). There has been a consensus that inhibition of smooth muscle cell proliferation can reduce intimal hyperplasia after angioplasty (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The lesions contain a fibromuscular cap covering a core composed of extracellular lipid and cell debris and show marked depositions of collagenous matrix. [37][38][39][40][41] In the present study we focused on the expression of network-forming collagen type VIII mRNA in comparison with fibrillar collagens (types I and III collagen), and in relation to TGF-␤1 and MMP-I in rabbit iliac arteries after a 1% cholesterol diet with and without previous balloon injury. 37,38 The mRNA expression was followed by in situ hybridization, for type VIII collagen also by northern blot analysis, and with immunohistochemistry to examine the corresponding protein.…”
mentioning
confidence: 99%